Dancing on Ruins: the allegorical architecture of IOOA - Henry Urbach (Oz, 1994)
The installations of Interim Office of Architecture work with pieces of modernity run amok. IOOA, as the name suggests, situates its projects at the interim—at once acknowledging the accumulated detritus of history and, at the same time, the possibility of repair.